Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2174/0929867327666201029161055
|View full text |Cite
|
Sign up to set email alerts
|

CypA: A Potential Target of Tumor Radiotherapy and/or Chemotherapy

Abstract: : Cyclophilin A (CypA) is a ubiquitous and highly conserved protein. CypA, the intracellular target protein for the immunosuppressant cyclosporine A (CsA), plays important cellular roles through peptidyl-prolyl cis-trans isomerase (PPIase). Increasing evidence shows that CypA is up-regulated in a variety of human cancers. In addition to being involved in the occurrence and development of multiple tumors, overexpression of CypA also has been shown to be strongly associated with malignant transformation. Surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Another report showed that PPIA could promote cancer metastasis in NSCLC through p38 MAPK 55 . In addition, the expression of PPIA is affected by chemotherapeutic drugs, and the overexpression of PPIA can render an organism resistant to chemotherapeutic drugs, which in turn become ineffective 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Another report showed that PPIA could promote cancer metastasis in NSCLC through p38 MAPK 55 . In addition, the expression of PPIA is affected by chemotherapeutic drugs, and the overexpression of PPIA can render an organism resistant to chemotherapeutic drugs, which in turn become ineffective 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the mechanism of this unique virus in NPC have not been fully illustrated. CYPA has been found to be overexpressed and involved in the development of several cancers such as colorectal cancer and breast cancer ( Chu et al., 2021 ; Davra et al., 2020 ; Yamamoto et al., 2020 ), and is regarded as a key player of human diseases ( Nigro et al., 2013 ). In the previous work of our laboratory, CYPA was found to be upregulated in both NPC tissues and sera exosomes ( Liu et al., 2019a ; Yang et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports and our research, the concentration of CYPA in patients with early ovarian cancer was significantly increased, compared with healthy women and benign group, and the proportion of CYPA positive reaction was higher in I/II stage. [8][9][10] In addition, the secretion of CYPA in serous ovarian cancer is much higher than that in nearby tissues, and the advanced of ovarian cancer is also closely related to the expression of CYPA. 10 All these indicate that the overexpression of CYPA is intimately associated with the occurrence of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%